Mode of action of the sesquiterpene lactones psilostachyin and psilostachyin C on trypanosoma cruzi - Sülsen, Valeria Patricia (2016)
Trypanosoma cruzi is the causative agent of Chagas' disease, which is a major endemic disease in Latin America and is recognized by the WHO as one of the 17 neglected tropical diseases in the world. Psilostachyin and psilostachyin C, two sesquiterpene lactones isolated from Ambrosia spp., have been demonstrated to have trypanocidal activity. Considering both the potential therapeutic targets present in the parasite, and the several mechanisms of action proposed for sesquiterpene lactones, the aim of this work was to characterize the mode of action of psilostachyin and psilostachyin C on Trypanosoma cruzi and to identify the possible targets for these molecules. Psilostachyin and psilostachyin C were isolated from Ambrosia tenuifolia and Ambrosia scabra, respectively. Interaction of sesquiterpene lactones with hemin, the induction of oxidative stress, the inhibition of cruzi-pain and trypanothione reductase and their ability to inhibit sterol biosynthesis were evaluated. The induction of cell death by apoptosis was also evaluated by analyzing phosphatidylserine exposure detected using annexin-V/propidium iodide, decreased mitochondrial membrane potential, assessed with Rhodamine 123 and nuclear DNA fragmentation evaluated by the TUNEL assay. Both STLs were capable of interacting with hemin. Psilostachyin increased about 5 times the generation of reactive oxygen species in Trypanosoma cruzi after a 4h treatment, unlike psilostachyin C which induced an increase in reactive oxygen species levels of only 1.5 times. Only psilostachyin C was able to inhibit the biosynthesis of ergosterol, causing an accumulation of squalene. Both sesquiterpene lactones induced parasite death by apoptosis. Upon evaluating the combination of both compounds, and additive trypanocidal effect was observed. Despite their structural similarity, both sesquiterpene lactones exerted their anti-T. cruzi activity through interaction with different targets. Psilostachyin accomplished its antiparasitic effect by interacting with hemin, while psilostachyin C interfered with sterol synthesis.